Residual stresses in environmental and thermal barrier coatings on curved superalloy substrates: experimental measurements and modelling - Liu, D.; Kyaw, S.T.; Flewitt, P.E.J.; Seraffon, M.; Simms, N.J.; Pavier, M.; Jones, I.A. (Elsevier, 2014)
Residual stresses within thermal barrier coated (TBC) systems are predicted using finite element models and are compared against experimental measurements taken using Raman and photo-stimulated luminescence piezo-spectroscopic methods. Two types of specimens were considered: flat specimens without TBC, and aerofoil shaped specimens with TBC. Comparisons between model predictions and experimentally measured stresses and also the relationship between substrate curvature and residual stresses on subsequent spallation of the aerofoil specimen were made. For the flat specimen, predicted and measured residual stresses are of the same order of magnitude. Both studies have indicated that larger compressive residual stresses arise from higher substrate curvatures. The results improve the understanding of initiation and propagation of TBC cracks which occurs preferentially at locations with high substrate convex curvature.